PENGARUH BUDAYA ORGANISASI; KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI - Santosa, Budi; Sugiyono, Sugiyono (Universitas Mercu Buana, 2017)
This research aims to examine and analyze the effects of organization culture; leadership; work motivation on employee performance at Indonesian Armed Forces Logistics staff. The method of research is quanlitative with quantitative approach. Data of of research is primary data for observation on April upto October 2015. The number of samples of this research was 54 respondents; consists of all ASN level. The method of analysis used in this research is Linear Regression with supporting tools SPSS 23.00 The results of this research showed that organization culture has significant influence to the employee’s performance; Leadership has significant influence to the employee’s performance; work motivation has significant influence to the employee’s performance; and organization culture; leadership and work motivation simultaneiusly affect the employee’s performance.